Ethnomedicinal plants used by Dhimal community of Rajghat, Morang - Baral, Bhumi Raj; Bhagat, Indramani (Nepalese Journal of Biosciences, 2018)
This work was carried out during 2015-2016. During study PRA technique and interview technique were employed to get ethnomedicinal information from local people. The study showed that Dhimals of Rajghat are ethnomedicinally very rich. They used different plants and parts of plants to recovery from different illness. Altogether 113 plant species were reported with their local name, short description, field notes and ethnobotanical notes used by Dhimals in medicinal purpose. These plant species were distributed under 102 genera and 55 families. Among them 44 families were belongs to dicotyledons, 9 families belong to monocotyledons and 2 families from pteridophytes. The largest family was Fabaceae with 12 species of medicinal purpose. Different 15 plant species were used to cure fever and another 15 species for cold and cough. More than one plant species were used by Dhimals to cure one illness. Similarly, more than one illness was cured by a single plant species. Dhimals used different parts of plants for medicinal purpose. They used leaves of 51 species, roots of 33 species and fruits of 21 species. Similarly, they also used seeds, flowers, trunks, barks, rhizome, latex, resin, etc. of plants for the treatment of different ailments. Dhimals of Rajghat have a great faith in the traditional healing system and they frequently visit the Dhamis for the treatment of most illness. Dhamis on the other hand, have a very sound knowledge on the use of herbal medicines.